개인의 사회적 요소들이 게임 수행에 미치는 영향 분석 - 최성락(Seong-Rak Choi); 박준휘(Junhwi Park) (한국콘텐츠학회 논문지, 18(4), 2018)
This study analyzes the influence of player's social factors on their game play. By conducting a survey of 1,000 general public in Korea, this study aims to understand how game player's social factors influence on their game play behavior: whether they play a game or not, how long they play, and how frequent they play. The survey result suggests that there are some relations between player's social factors and their game play behaviour. The personal factors such as sex, age, monthly income level are seen to have influence on the length and frequency of their game play. Players' the social factors such as social status, social activity participation level and confidence level also have influence over their game play behaviours as well. And the influences are seen to be different depending on whether it's on online game or mobile game. 본 연구에서는 개인의 사회적 요소들이 게임 수행에 영향을 미치는지에 대한 여부를 살펴보았다. 개인의 성별, 연령, 최종학력, 월평균 소득 등의 요소와 개인이 인지하는 개인의 사회적 위치, 타인에 대한 신뢰도, 사회활동 참여 여부, 행복도 등이 게임 경험 여부, 게임 시간, 게임 이용 빈도 등에 영향을 미치는가에 대한 여부를 분석하였다. 조사 방법으로는 설문 조사가 실시되었으며, 국민 1,000명을 대상으로 수행되었다. 분석 결과 성별, 연령, 가구 월평균 소득 등은 게임 경험 여부, 게임 시간 등에 영향을 미치고 있었다. 또한 사회활동 참여 여부, 개인의 사회적 위치, 타인에 대한 신뢰도 등도 게임 관련 요소들에 영향을 미치고 있었다. 그리고 이러한 영향은 온라인 게임인가 모바일 게임인가에 따라서도 서로 다른 영향을 미치고 있는 것으로 나타났다. 또한, 월평균 소득, 사회활동 참여 등이 증가하고 타인에 대한 신뢰도가 낮을 경우 게임시간 및 이용 빈도가 증가하였다. 이러한 분석 결과를 통해 게임회사에서는 게임 이용자 요인을 고려하여 게임 구조를 보다 개선할 수 있을 것이다.